Autonomy in English learning and its relationship with independent works assigned to students - Cabrales Vargas, Myriam; Cáceres Cabrales, Jaime Andrés; Feria Marrugo, Irina Margarita (Íkala, Revista de Lenguaje y Cultura, 2010)
The objective is to analyze the influence of learning practices and independent assignments, on the development of the autonomy of the students of the English basic cycle of the Modern Languages program. Descriptive and correlational investigation was used, which by means of quantitative and qualitative interpretation of data relates the variables in the study, to determine its influence on the development of autonomy in students. Though some of them (25%) are autonomous, the rest do not reach this characteristic, due to little control exercised on their learning processes and because the tasks that are assigned to them do not help in the development of autonomy. The conclusion is that the strengths found in relation to the motivation of the students, their satisfaction with the program and their interest in ICT, are factors that if promoted, would contribute to the development of autonomy, work that has already begun and is commented on at the end of this article.